2017
DOI: 10.1002/hep4.1049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and economic burden of extrahepatic manifestations of hepatitis C virus are underestimated but can be improved with therapy

Abstract: Despite guideline recommendations, access to hepatitis C virus (HCV) treatment is frequently restricted, with some payers approving therapy for only those with advanced disease or cirrhosis. However, delaying potentially curative treatment until the development of advanced liver disease may have costly consequences in terms of both hepatic complications and extrahepatic manifestations (EHMs) of HCV. Using a large claims database from the United States, we measured the risks and medical costs of 20 EHMs and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 31 publications
(63 reference statements)
5
50
0
Order By: Relevance
“…Although we did not observe decreased costs in the DAA group among patients without cirrhosis, we believe that over time the savings associated with the avoidance of advanced liver disease and other complications of HCV will be offset, as predicted by several economic investigations in which DAA therapy was found to be cost‐effective in the long term . Furthermore, although we did not study HCV‐associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all‐cause medical costs were attributable to extrahepatic manifestation–related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure …”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Although we did not observe decreased costs in the DAA group among patients without cirrhosis, we believe that over time the savings associated with the avoidance of advanced liver disease and other complications of HCV will be offset, as predicted by several economic investigations in which DAA therapy was found to be cost‐effective in the long term . Furthermore, although we did not study HCV‐associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all‐cause medical costs were attributable to extrahepatic manifestation–related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure …”
Section: Discussionsupporting
confidence: 47%
“…Despite guideline recommendations, access to HCV treatment has been frequently restricted because of the high DAA drug costs and prior authorization policies in which only the sicker get treated, slowing the expected rise in treatment rates . This delay in potentially curative treatment until development of advanced liver disease may have costly consequences …”
mentioning
confidence: 99%
“…Delaying HCV treatment can impact disease progression to cirrhosis, hepatocellular carcinoma, liver‐transplant and liver‐related death. It is possible to significantly reduce this clinical and economic burden through viral eradication, especially if treatment is initiated early and not delayed until fibrosis advances …”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed a high burden of HCV-associated extrahepatic diseases (EHDs) and a decrease in all-cause medical costs post-SVR, which was largely attributed to decreased EHD-related spending. (8) It is therefore possible that the survival benefit noted in the current study was partially mediated through diminished chronic inflammation.…”
mentioning
confidence: 87%